Associations of in-hospital postpartum feeding experiences with exclusive breastfeeding practices among infants in rural Sichuan, China - Ann M. Weber; Yian Guo; Evelyn Zhang; Susan Gruber; Alexis Medina; Huan Zhou; Gary L. Darmstadt (BMC, 2023)
Abstract Background In rural China, exclusive breastfeeding (EBF) prevalence is low and hospitals often fail to attain baby-friendly feeding objectives, such as ≥ 75% of newborns exclusively breastfed from birth to discharge. Empirical evidence for the impact of increased hospital compliance with recommended feeding guidelines on continued EBF in rural China is lacking. We sought to measure and model the association of newborns' in-hospital feeding experiences with EBF practice in infancy to inform policies for EBF promotion. Methods Data were cross-sectional from 785 caregivers of infants < 6 months of age, collected from November to December 2019 in four underdeveloped counties/districts in Sichuan Province. In-hospital feeding practices were determined, and prevalence of current infant feeding practices was calculated from 24-h recall and categorized according to WHO/UNICEF Infant and Young Child Feeding categories as EBF, breastfed with non-milk liquids, mixed feeding, breastfed with solids, and not breastfed. Relative risk ratios were estimated using adjusted multinomial logistic regression to examine risk factors for non-EBF practices compared to EBF, including in-hospital feeding experiences. The regression model was used to investigate change in EBF prevalence under alternative in-hospital experiences. Results Only 38.1% of under-six-month-old infants were being exclusively breastfed when data were collected; 61.8% and 77.6% had been fed water and infant formula, respectively, in the hospital. Infants who were fed water or formula before discharge were estimated as 2-3 times as likely to be non-EBF than EBF up to age six months. According to our model, EBF prevalence would have increased to 53.7% (95% confidence interval (CI) 46.1, 61.2) had ≥ 75% of infants been exclusively breastfed and water-based feeds eliminated in-hospital. Conclusions Given the importance of infants' first feeding experiences in the establishment and continuation of EBF, it is imperative that rural Chinese hospitals actively seek to limit infant formula feeds to medically indicated situations and eliminate water-based feeds.